Conditions for the existence of solutions of real nonautonomous systems of quasilinear differential equations vanishing at a singular point - Evtukhov, V. M.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We establish conditions for the existence of solutions vanishing at a singular point for various classes of systems of quasilinear differential equations appearing in the investigation of the asymptotic behavior of solutions of essentially nonlinear nonautonomous differential equations of higher orders.